Allelic association of G72/G30 with schizophrenia and bipolar disorder: a comprehensive meta-analysis - Shi, Jiajun (2007)
The G72/G30 gene complex (G72 also known as D-amino acid oxidase activator, DAOA) and its chromosomal region 13q32–34 have been linked and associated with both schizophrenia (SCZ) and bipolar disorder (BP) in multiple studies, including our initial association report on BP. However, the inconsistency of associated variants across studies is obvious. Previous meta-analyses had small data sets. The present meta-analysis combined 18 association articles published before April of 2007. There were 19 independent studies of SCZ, with 4304 cases, 5423 controls, and 1384 families, and four independent studies of BP with 1145 cases, 1829 controls, and 174 families. Of 15 single nucleotide polymorphisms (SNPs) analyzed in the 95-kb G72/G30 gene region, M18/rs947267 and M22/rs778293 showed association with SCZ in Asians, and M24/rs1421292 with SCZ in Europeans. The associations of C allele at M18 and A allele at M22 with SCZ in Asians survived conservative Bonferroni correction for multiple testing for 15 markers and subgroup analysis (adjusted P = 0.0000253 for M18; adjusted P = 0.009 for M22). No single maker showed evidence of overall association with BP. These results suggest that G72/G30 may influence susceptibility to schizophrenia with weak effects.